International and foreign legal research : a coursebook - Hoffman, Marci (Martinus Nijhoff Publishers, 2012)
International and Foreign Legal Research: A Coursebook, second edition by Hoffman and Rumsey, now in a second edition, is designed for classes in foreign and international legal research. Topics covered in the book range from treaty research to chapters on particular subjects of international law. Coverage also includes chapters on researching foreign and comparative law as well as major international organizations, including the UN and the EU.
Keywords: Legal research.; International law -- Legal research.; Droit -- Recherche documentaire.; LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; International law -- Legal research; Legal research; Foreign law.; Comparative law.; Customary international law.; Sources of law.; International law.